Analisis Praktik Penghindaran Pajak Sebelum dan Dimasa Pandemi Pada Perusahaan Sub Sektor Perdagangan Besar Terdaftar Di BEI Tahun 2018-2021 - Muh Bahri; Syaikhul Falah; Hesty Theresia Salle (Jurnal Akuntansi dan Pajak, 2024)
This study aims to analyze tax avoidance before and during the pandemic, this study uses a quantitative approach using secondary data. The sample selection uses purposive sampling with a population of large trading sub-sector companies listed on the IDX in 2018-2021. Tax avoidance is measured by the ETR proxy, and Current ETR. Hypothesis testing using SPSS software by performing different tests. Paired sample t-test for normally distributed data and Wilcoxon test for data that are not normally distributed. In accordance with attribution theory, when a company responds consistently to its decision making in different situations, it is likely that tax avoidance practices tend to be carried out due to internal company factors. The concept of a new public service which views taxpayers as citizens who receive and use tax services and at the same time as the subject of regulations that regulate tax obligations are able to carry out their obligations, the absence of differences in tax avoidance is influenced by the existence of online-based tax facilities that make taxpayers still able to carry out their duties. His tax obligations during the pandemic are also supported by regulations on tax avoidance which are also able to minimize tax avoidance.